2000
DOI: 10.1046/j.1471-4159.2000.0742622.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning of a Novel Brain‐Type Na+‐Dependent Inorganic Phosphate Cotransporter

Abstract: Abstract:We have isolated a human cDNA encoding a protein, designated DNPI, that shows 82% amino acid identity and 92% similarity to the human brain-specific Na ϩ -dependent inorganic phosphate (Na ϩ /P i ) cotransporter (BNPI), which is localized exclusively to neuron-rich regions. Expression of DNPI mRNA in Xenopus oocytes resulted in a significant increase in Na ϩ -dependent P i transport, indicating that DNPI is a novel Na ϩ /P i cotransporter. Northern blot analysis shows that DNPI mRNA is expressed predo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
214
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 246 publications
(223 citation statements)
references
References 19 publications
8
214
0
1
Order By: Relevance
“…In contrast to Arg 184 , this residue is conserved only in members of the VGLUT family, suggesting a specific role for L-glutamate transport. Replacement of Arg 88 in TM1, which is conserved in VGLUTs, NPT1, NPT3, and sialin (19,20,35,36), with alanine decreased the ATP-dependent uptake activity to 74% of the wild type. Replacement of Glu 191 in TM4, which is conserved in VGLUTs and sialin, with aspartate, glutamine, and alanine, decreased the ATP-dependent activity to 39, 27, and 7% of the wild type, respectively (Fig.…”
Section: Table 1 Reconstitution and The Effects Of Various Ligands Onmentioning
confidence: 97%
See 1 more Smart Citation
“…In contrast to Arg 184 , this residue is conserved only in members of the VGLUT family, suggesting a specific role for L-glutamate transport. Replacement of Arg 88 in TM1, which is conserved in VGLUTs, NPT1, NPT3, and sialin (19,20,35,36), with alanine decreased the ATP-dependent uptake activity to 74% of the wild type. Replacement of Glu 191 in TM4, which is conserved in VGLUTs and sialin, with aspartate, glutamine, and alanine, decreased the ATP-dependent activity to 39, 27, and 7% of the wild type, respectively (Fig.…”
Section: Table 1 Reconstitution and The Effects Of Various Ligands Onmentioning
confidence: 97%
“…Mutational Analysis-Recent analyses of structure-function relationship of membrane transporters have pointed out the functional importance of the conserved charged amino acid residues in transmembrane domains. The topological model of VGLUT2 predicts twelve transmembrane spanning helices (26); several charged amino acid residues have been identified that are conserved in these putative transmembrane regions of the SLC17 or VGLUT families (19,20,35,36). We focused on five amino acid residues, Arg 184 and Glu 191 in transmembrane segment 4 (TM4), Arg 88 in TM1, His 128 in TM2, and Arg 322 in TM7 and introduced mutations in these amino acid residues (Fig.…”
Section: Expression Purification and Reconstitution Of Vglut2-mentioning
confidence: 99%
“…Since the culture medium might be one of limiting factors on synapse saturation, it will be necessary to confirm the saturation process using other culture conditions. Previous molecular biological studies have identified three subtypes of VGluT: VGluT1, VGluT2, and VGluT3 (Ni et al, 1994;Aihara et al, 2000;Gras et al, 2002).…”
Section: Saturation Of Vglut1-and Vgat-immunopositive Synaptic Densitmentioning
confidence: 99%
“…These transporters mediate glutamate uptake into synaptic vesicles and are driven by a proton electrochemical gradient generated by the vacuolar H ϩ -ATPase (1)(2)(3)(4)(5)(6)(7)(8)(9). VGLUTs were initially identified as members of the type I Na ϩ ͞inorganic phosphate transporter family (10,11). Although other vesicular neurotransmitter carriers also depend on the activity of the vacuolar H ϩ -ATPase, they belong to distinct protein families, one containing the vesicular ␥-aminobutyric acid (GABA)͞ glycine transporter and the other the vesicular monoamine transporters as well as the vesicular acetylcholine transporter (12).…”
mentioning
confidence: 99%